The Relationship Between Rising Credit Risks and Economic Crises - Murad Abbas oğlu Məmmədov (Scientific Results, 2024)
Credit risk refers to the possibility that a borrower will not be able to meet its obligations. An increase in this risk could seriously affect the financial health of banks and the broader economic environment. Credit risks usually increase during economic crises, as economic downturns, unemployment, and declining production worsen borrowers’ ability to pay. This article examines the relationship between the increase in credit risks and economic crises, adds the effects of the global financial crisis, and discusses the role of devaluation in the economic context of Azerbaijan.